2020
DOI: 10.1073/pnas.1913970117
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies key modulators of complement factor H binding to malondialdehyde-epitopes

Abstract: Genetic variants within complement factor H (CFH), a major alternative complement pathway regulator, are associated with the development of age-related macular degeneration (AMD) and other complementopathies. This is explained with the reduced binding of CFH or its splice variant factor H-like protein 1 (FHL-1) to self-ligands or altered self-ligands (e.g., malondialdehyde [MDA]-modified molecules) involved in homeostasis, thereby causing impaired complement regulation. Considering the critical role of CFH in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 54 publications
3
34
0
1
Order By: Relevance
“…Binding of FHR-1 and FHR-5 to cells depends on available receptors and surface ligands; for example, previously we did demonstrate FHR-1 binding to viable neutrophils via the complement receptor CR3 ( 60 ). On necrotic cells, malondialdehyde epitopes represent one of the ligands of FHR-1 and FHR-5, and both FHRs were shown to enhance complement activation when bound to malondialdehyde epitopes in vitro ( 57 , 61 ). The inhibition of FHR-1 and FHR-5 binding to necrotic cells by dNTP and their partial co-localization with DNA suggest that DNA could serve as an additional ligand for both FHRs on necrotic cells ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of FHR-1 and FHR-5 to cells depends on available receptors and surface ligands; for example, previously we did demonstrate FHR-1 binding to viable neutrophils via the complement receptor CR3 ( 60 ). On necrotic cells, malondialdehyde epitopes represent one of the ligands of FHR-1 and FHR-5, and both FHRs were shown to enhance complement activation when bound to malondialdehyde epitopes in vitro ( 57 , 61 ). The inhibition of FHR-1 and FHR-5 binding to necrotic cells by dNTP and their partial co-localization with DNA suggest that DNA could serve as an additional ligand for both FHRs on necrotic cells ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A polarized monolayer could be detected for untreated and FHR3 treated cells, showing that FHR-3 had no effect on stable cell-cell contacts. We also excluded that ARPE- 19 Due to the number of passages and the slight EMT, which is typical for aged human RPE cells (38), the investigated ARPE-19 cells P38 were termed senescent cells in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Just recently, it was shown that FHR-3 binds to malondialdehyde (MDA)-epitopes (19). These OSE are present on the surface of stressed ARPE-19 cells (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we recently demonstrated that genetic deletions of complement factor H-related protein 1 (CFHR1), which was previously shown to bind to MDA-LDL ( 82 ), and 3 (CFHR3) affects the ability of plasma CFH to bind MDA surfaces. Moreover, purified CFHR1 and CFHR3 competes with CFH for binding to MDA-epitopes ( 83 ). Our findings indicate the influence of genetic variations within the CFH/CFHR1/CFHR3 locus on the recognition and binding of OSEs, thereby affecting outcome in diseases associated with oxidative stress and aging such as NAFLD.…”
Section: Introductionmentioning
confidence: 99%